A generalized logistic function and its applications - Grzegorz Rządkowski; Lidia Sobczak (Foundations of Management, 2020)
In the present article, we deal with a generalization of the logistic function. Starting from the Riccati differential equation with constant coefficients, we find its analytical form and describe basic properties. Then we use the generalized logistic function for modeling some economic phenomena.
Keywords: C53; 650; generalized logistic function; time series; applications